Health and Writing: Meaning-Making Processes in the Narratives of Parents of Children With Leukemia. (March 2015) - Freda, Maria Francesca; Martino, Maria Luisa
There is literary evidence stating that expressive writing affects health outcomes. Nevertheless, the processes underlying its benefits remain unclear. In our previous article, we described the benefits of writing; in this article, we investigate the meaning-making processes underlying the traumatic experiences of parents of children with leukemia in off-therapy. We collected the writings of 23 parents and grouped them according to the parents' psychological outcome (low/good/high) with respect to anxiety, as assessed during a follow-up. We qualitatively analyzed the texts written by parents with good psychological outcomes to highlight their main meaning-making processes, that is, how they put into words the shattering experience, reordered the events, connected their emotions and the events, reevaluated the event, and reconstructed the time process. We found that parents with low/high outcomes articulated these processes differently. Furthermore, we discussed the uses and functions of written narration for each group.